Islam, IAIN, dan Pengembangan Kewiraswastaan - Musa Asyárie (Al-Jami'ah Research Centre, 1996)
Entrepreneurship is a process of an autonomous enterprise which gained through the rise and fall of enterprise as well as commitment on exemplification and morality in relation to all process of entrepreneurship. It needs work ethos which is accumulated from social, economies, cultural and religious values. Among these values, the religious part is the most important and become its fundamental basis. Since religion is the most important and become its fundamental basis. Since religious is the fundamental part of enterprise, therefore one of the main motivations and purposes of a real entrepreneur is devotion to God. Whenever someone comes into an entrepreneurship world. There are at least four interrelated thing which ought to be noticed, they are: production, marketing, finance and human resources. In addition, there are steps before entering this world; 1) self-recognition of the available potentials, its weaknesses and strengths. 2) recognition of economical potentials. Of his/her surroundings. 3) accretion of economical analysis before choosing a kind of enterprise and followed by empirical experiment. 4). Horizontally and then vertically expansions of the enterprise after the empirical experiment showed a positive result. According to the Qur’an, human being is a functional unity of ‘abd (Slave) and Khalīfā (vicegerent). ‘abd is marked by obeying religious morality, while khalīfā is marked by his creativity in making concept and realizing it in his worldly life. In relation to this fact. There is no dual knowledge in Islam. Knowledge in Islam is monotheistic as unity and integrality of the existence of god’s reverence and generosity. For this reason, Islamic education must be built on the basis of human philosophy and science philosophy which are monotheistic. Human philosophy is need to formulate the concept of the ideal human being according to the Qur’ān. Philosophy of science is needed to develop human ability in making concept and its realization of turning culture for the welfare of human being on earth. Based on this understanding, the activities for heavenly life are embodied in worldly life. Thus, the essence of work ethos of mankind as God's successors is realizing that the duty of life is to work for God adoration as a kind of confession of being the slave of Allah. To create functional human being, as slave as well as vicegerent of God. the role of IAIN should be put on a broader perspective in the process of national development the role is not only related to its institutional status as a center of education and center of preparing human resources for spiritual development, but also as a center of education which produce qualified entrepreneurs who struggle for strengthening their faith The involvement of IAIN in the effort of empowering society is, in fact, a call of religion Therefore, IAIN needs to give opportunities to students who choose entrepreneurship as their career by giving provisions which are programed through steps: training, apprenticeship. Writing proposal. capitalization. partnership, and being entrepreneur in relation to this idea. The utilization of student cooperative should be optimized. while in accordance with developing staff welfare, their cooperative should be professionalized.